2015
DOI: 10.1002/jbm.a.35510
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of permselective PVA hydrogels with mixed ECM analogues

Abstract: The presentation of multiple biological cues, which simulate the natural in vivo cell environment within artificial implants, has recently been identified as crucial for achieving complex cellular functions. The incorporation of two or more biological cues within a largely synthetic network can provide a simplified model of multifunctional ECM presentation to encapsulated cells. Therefore, the aim of this study was to examine the effects of simultaneously and covalently incorporating two dissimilar biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…This photoinitiator was shown to be much less cytotoxic than DMPA , for a similar reactivity with (meth)­acrylate moieties. It has been widely used for synthesizing porous photopolymerized hydrogels for biomedical purposes. However, its drawbacks lie in its low molar absorption coefficient and the need of UV light that may be detrimental to living cells …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This photoinitiator was shown to be much less cytotoxic than DMPA , for a similar reactivity with (meth)­acrylate moieties. It has been widely used for synthesizing porous photopolymerized hydrogels for biomedical purposes. However, its drawbacks lie in its low molar absorption coefficient and the need of UV light that may be detrimental to living cells …”
Section: Methodsmentioning
confidence: 99%
“…Generally, the grafting of polymerizable groups is made by reaction of hydroxyl or amine functions borne by the polymeric precursor with (meth)­acryloyl chloride, (meth)­acrylic anhydride, (meth)­acrylic acid (in the presence of EDC and NHS), or glycidyl methacrylate. Many researchers have also associated two or more polymers to form a conetwork or interpenetrated polymer networks (IPNs). ,,,,,,,,,,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[140] In certain cases, the hydrophilic and anti-fouling properties of electroconductive hydrogels prevent cell attachments, [141] which can be mitigated by functionalizing hydrogels with molecules such as gelatin and sericin to promote neuronal attachment and growth. [142] As such, hydrogels can be modified post-fabrication with chemical functionalization [143] and surface modifications to strengthen bonding and covalent interactions between hydrogels and neuroprosthetic devices. [34] These modifications can direct the responses of hydrogels to electric fields and guide their interactions with surrounding cells.…”
Section: Fabricating Electroresponsive Hydrogel Composites For Neural...mentioning
confidence: 99%
“…The ultra violet (UV) photopolymerized PVA hydrogels were prepared via methacrylated functionalization, and the effects of incorporation of heparin and GEL within a PVA hydrogel were examined. 167 Chen et al advanced the novel double network PEG/COL, whose mechanical strength could be modified by changing the rigidity, molecular weight, and crosslinking density of the two components. Results indicated that the incorporation of COL significantly enhanced the strength and toughness of hydrogels.…”
Section: Hydrogel Scaffoldsmentioning
confidence: 99%